Assessment of population parameters of some selected fishes in Pahang coastal water and Kuantan river for their proper management - Rahman, Mohammad Mustafizur; Sabuti, Asnor Azrin; John, Akbar (2018)
Pahang coastal water is very rich in term of fisheries resource. It is a habitat for many economically important fishes. However, the productions of many fishes are decreasing very rapidly in the Pahang coastal water and Kuantan river. This puts an increasing demand on the study and management of these economically important fishes. Unfortunately, up to our knowledge, there is no information about why the stocks of these fishes are decreasing from these habitats. However, adequate information about population parameters of these fishes is prerequisite for their management. Therefore, a study was conducted to determine some important population parameters particularly growth, abundance, condition factor, hepatosomatic index, fecundity and spawning of these fishes, and to make a recommendation for the management of these economically important Fishes. For this study, the length-frequency data of all fishes were recorded from the commercial catches from Kuantan landing sites (LKIM). Growth, abundance, condition factor, hepatosomatic index and spawning season were determined in the Marine Laboratory of Kulliyyah of Science, IIUM from collected samples. The results of the study are helpful to prepare a management policy of these economically important fishes. Therefore, the results of this study are very important for (i) preparing a management policy of this fishes, (ii) food security and (iii) economic benefits of Malaysia. The project has produced several articles which are published in Scopus and ISI indexed international Journals. A master student has also been graduated under this project.